(untitled) (NPRC Journal of Multidisciplinary Research, 2024)
Rapid infrastructure development in Nepal, has created economic opportunities but poses significant challenges for natural resource conservation. This article examines the policies and practices currently in place to protect Nepal’s natural resources during infrastructure development, highlighting gaps and opportunities for improvement. It explores the role of Environmental Impact Assessments (EIAs), legal frameworks, and community engagement in minimizing ecological damage from projects such as roads, hydropower, and urban development. Findings reveal that while Nepal has implemented some conservation policies, inconsistencies in enforcement, limited community involvement, and insufficient eco-friendly practices compromise environmental sustainability. The study recommends strengthening policy frameworks, enhancing EIA processes, promoting eco-friendly infrastructure practices, and fostering public-private partnerships to achieve a balanced approach. With effective conservation strategies, Nepal can progress towards a sustainable model of development that safeguards its diverse ecosystems while supporting economic growth.